Research on System Performance of Air-source Transcritical CO2 Heat Pump - Zhao Zongbin; Song Yulong; Bao Jihu; Lu Lei; Li Hongzhe; Guo Yang; Zhu Fenglei (Zhileng xuebao)
Based on a theoretical analysis of an air-source transcritical CO2 heat pump system, a mathematical model for the compressor was developed using an efficiency analysis in this study. In addition, a mathematical model for the expansion valve was built using a structural analysis; and mathematical models for the gas-cooler, evaporator, and regenerator were developed using the distributed parameter method. Moreover, a mathematical model for the entire system was built by combining these models. The accuracy of the system model was verified by an experimental test, which showed that the deviation in the unit’s input power between the calculated value and measured value was less than 4.4%, the mean deviation in the heating capacity was 5.76%, and the deviation in the optimal discharge pressure was less than 0.1 MPa. Thus, it was possible to calculate the system performance by employing the mathematical simulation method.